Seed Dry Weight, Leaf Area and Photosynthetic Rate in Relation to Dry Biomass of Five Tree Species in the Nursery Stage - Geneshan, K. P.; Unnikrishnan, K. (Indian Forester, 1999)
Promptly implementing long term programmes of fundamental biological research are essential for the innovative economic and timely exploitation of biomass. Trials were conducted to find out the interrelationship of dry seed weight, leaf area and photosynthetic rate on one hand and of biomass on the other in Pongamia glabra, Macaranga peltata, Veteria indica, Syzygium cumini and Mimusops elengi. V. indica showed maximum dry weight of seed and leaf area. But the photosynthetic rate was moderate throughout the day. P. glabra and M. elengi showed relatively high photosynthetic rate for a long time. In all the species stomatal resistance did not show any definite trend with photosynthetic rate. The highest dry biomass was noticed in M. peltata and V. indica after one year of growth. All these show the lack of clear cut interaction of leaf area, seed dry mass and photosynthetic rate for seedling biomass predictions.